Faith as a theme in Mark's narrative - Marshall, Christopher David (Society for New Testament Studies monograph series, 1989)
Mark's gospel has attracted an enormous amount of scholarly attention over recent decades. The major themes of the gospel have been studied exhaustively and from a variety of critical perspectives. But at least one important theme in Mark has been comparatively neglected in recent study, the theme of faith. This critically acclaimed book redresses such neglect through a thorough exegetical and literary study of all the references to faith in Mark's composition.